Pengaruh Model Pembelajaran Cooperative Script Terhadap Keaktifan Belajar Pak Siswa Kelas VIII SMP Negeri 3 Lintongnihuta Tahun Pembelajaran 2022/2023 - Kristiani Sinaga; Lince R.T Simamora; Rawatri Sitanggang (Universitas Katolik Widya Karya Malang, 2023)
The aim of this research is to determine the positive and significant influence of the Coperative Script learning model on the active learning of PAK students in Class VIII of SMP Negeri 3 Lintongnihuta for the 2022/2023 academic year. The method used in this research is quantitative descriptive, with a population of all class VIII students at SMP Negeri 3 Lintongnihuta totaling 191 people and a sample of 48 people, namely 25% of the total population. Data was collected using a positive closed questionnaire of 40 items, of which 25 questionnaire items were for variable 2022/2023 Academic Year: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.493 > rtable(a=0.05,n=48) = 0.284, thus it is known that there is a positive relationship between variable X and variable Y. b) Testing a significant relationship, the value obtained is tcount= 3.839 > ttable(a=0.05,dk=n-2=46)= 2.021, thus there is a significant relationship between variable X and variable Y. 2) Test the influence : a) Test the regression equation, obtained the regression equation Y ̂=